Mr. Blackwell exhibit planning materials - Unidentified author (Colorado State University. Libraries, 1996)
Schedule for "Outrageous Mr. Blackwell" events for November 6-10, 1996. Includes typed and handwritten notes.
Full name of exhibit event is The Premier Showing of a Collection of Outrageous Designer Gowns by Mr. Blackwell.
Keywords: Fashion -- History; Fashion -- Exhibitions